2010
DOI: 10.1111/j.1525-1470.2010.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasiform Type of Lichen Scrofulosorum: Clue to Disseminated Tuberculosis

Abstract: We present a 16-year-old girl with tuberculosis of the lungs, lymph nodes, and liver, who had extensive inflammatory lesions with pustules, which resembled psoriasis. A skin biopsy showed extensive tuberculoid granulomas surrounding hair follicles, consistent with lichen scrofulosorum. Antitubercular therapy led to resolution of skin lesions. This severe inflammatory type of lichen scrofulosorum is extremely rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…11,12 A psoriasiform subtype of lichen scrofulosorum characterized by erythematous scaling papules and plaques with interspersed pustular lesions has been documented in patients with extrapulmonary TB. 13,14 Our patient similarly had extrapulmonary TB and psoriasiform lesions; however, there were no papular lesions, which have been reported in cases of psoriasiform variant lichen scrofulosorum, and a lack of periadnexal granulomas.…”
Section: Discussionsupporting
confidence: 54%
“…11,12 A psoriasiform subtype of lichen scrofulosorum characterized by erythematous scaling papules and plaques with interspersed pustular lesions has been documented in patients with extrapulmonary TB. 13,14 Our patient similarly had extrapulmonary TB and psoriasiform lesions; however, there were no papular lesions, which have been reported in cases of psoriasiform variant lichen scrofulosorum, and a lack of periadnexal granulomas.…”
Section: Discussionsupporting
confidence: 54%
“…Lichen scrofulosorum (LS) is a classical tuberculid due to hypersensitivity reaction to Mycobacterium tuberculosis/bovis that presents with asymptomatic, closely grouped, skincolored to erythematous, perifollicular papules in children and adolescents with tuberculosis. 1,2 The diagnosis may be challenging as the presentation is varied and mimics several other dermatological conditions, including micropapular lichen planus, lichen nitidus, lichen spinulosus, keratosis pilaris, sarcoidosis, and id eruption. 3 Koebner phenomenon (KP), first described by Heinrich Koebner, is the induction of isomorphic pathologic lesions in traumatized uninvolved skin of patients with cutaneous diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al . reported multiple TB foci in the lung, abdomen, and liver in the same patient with LS . Therefore, a thorough systemic evaluation should be undertaken to detect concurrent focus of TB in all the patients diagnosed with LS.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Kumar et al reported multiple TB foci in the lung, abdomen, and liver in the same patient with LS. 15 Therefore, a thorough systemic evaluation should be undertaken to detect concurrent focus of TB in all the patients diagnosed with LS. In this report, absence of conventional TB foci in lymph nodes, lung, skin, and bones, and history of infertility in both the patients prompted us to evaluate them for endometrial TB.…”
Section: Discussionmentioning
confidence: 99%